Upaya Ditpolairud Polda Riau Dalam Pencegahan Transnational Crime Penyelundupan Narkotika Di Jalur Laut Riau - Ditya Riantiarni; M. Zulherawan (Sisi Lain Realita Another Side Of Reality Journal Criminology, 2025)
The increase in cross-border crimes, especially narcotics smuggling through the sea route in the Riau region, is a serious threat to public security and order. Riau's geographical location is close to international waters making it one of the vulnerable points for the entry of narcotics networks from abroad. This study aims to examine the efforts of the Riau Regional Police Directorate in preventing narcotics smuggling through the sea route by focusing on prevention strategies, operational constraints, and the level of effectiveness. The method used is a qualitative approach with data collection techniques in the form of interviews, observations, and documentation. The results of the study show that prevention is carried out through routine patrols, cooperation with related agencies, supervision of vulnerable areas, and the involvement of coastal communities. However, there are still obstacles in the form of limited facilities, the breadth of the supervision area, and the development of the perpetrator's modus operandi. Overall, the efforts made reflect an adaptive preventive approach in dealing with narcotics crimes.